Within-person, between-person and seasonal variance in nutrient intakes among 4- to 8-year-old rural Zambian children - Caswell, Bess L.; Talegawkar, Sameera; Siamusantu, Ward; West Jr., Keith P.; Palmer, Amanda (Cambridge University Press, 2020)
Estimates of the components of nutrient intake variation are needed for modelling distributions of usual intake or predicting the usual intake of individuals. Season is a potential source of variation in nutrient intakes in addition to within- and between-person variation, particularly in low- or middle-income countries. We aimed to describe seasonal variation in nutrient intakes and estimate within-person, between-person and other major components of intake variance among Zambian children. Children from rural villages and peri-urban towns in Mkushi District, Zambia aged 4–8 years were enrolled in the non-intervened arm of a randomised controlled trial of pro-vitamin A carotenoid biofortified maize (n 200). Up to seven 24-h dietary recalls per child were obtained at monthly intervals over a 6-month period covering the late post-harvest (August–October), early lean (November–January) and late lean (February–April) seasons (2012–2013). Nutrient intakes varied significantly by season. For